PROSES PEMBUATAN PASTA BAWANG MERAH (Allium cepa var. aggregatum) DAN PENENTUANUMUR SIMPANNYADALAM KEMASAN GELAS - Niken Ayu Permatasari, Indah Yuliasih, dan Ani Suryani (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
Shallot is a commodity that is widely used as a spice. The unstable supply and price of shallot causes it requires some further processing. The alternative of shallot processing is shallot paste. The aims of this study wereto develop shallot paste formula which had a strong aromaas well as determination of shelf life in a glass jar. This study has several steps, i.e. preparation and characterization of fresh shallot, processing shallot paste, and determination of shelf life shallot paste in glass jar with the ESS (Extended Storage Studies) method. This main research used completely randomized design with two factors: first, the ratio of fresh shallot and shortening, and second, emulsifier concentration. The ratio of fresh shallot and shortening were 2:1, 3:1 and 4:1 with emulsifier concentration of 2, 3 and 4% for each ratio of fresh shallot and shortening. The statistical analysis showed that the ratio of fresh shallot and shortening affected theFFA (free fatty acid) value. Concentration of emulsifier and interaction between emulsifier concentration and ratio of fresh shallot and shortening affected VRS (volatile reducing substance) content of shallot paste. The best shallot paste treatment determined was the ratio of fresh shallot and shortening of 3:1 with emulsifier concentration of 4%. Shelf-life of packaged shallot paste in glass jar was 10 days at temperature 30, 40 and 50oC. During the storage, FFA value increased and VRS value decreased along with the increase in storage temperature. The increased of FFA value was caused by fat hydrolysis during storage, while the VRS value decreased due to the evaporation of sulfur compounds as flavor components in shallot paste during stir frying. Keywords : shallot paste, emulsifer, shortening, shelf life